High diversity of Caligus species (Copepoda: Siphonostomatoida: Caligidae) in Taiwanese waters - Ho, Ju-Shey; Lin, Ching-Long; Liu, Wei-Cheng (Zootaxa, 2016)
Caligidae, commonly known as sea lice, is the most speciose family of symbiotic copepods comprising over 490 species classified in 31 genera. Caligus Müller, 1785 is the largest genus of this family comprising 255 species. Fifty-three species of Caligus have been reported from Taiwan so far, representing 20.78 % of Caligus currently known in the world. Nevertheless, we believe many more species of Caligus are yet to be discovered from the waters of Taiwan, because only 17.71 % (553/3,121 species) of the potential fish hosts occurring in Taiwanese waters have been examined for parasitic copepods so far. Among the countries in the Far East, Taiwan exhibits the shortest coastline yet displays the highest diversity of Caligus species. This seemingly contradictory phenomenon may be explained by the fact that the Island of Taiwan is straddling over the border of two ecological realms in the western North Pacific, viz. the Temperate Northern Pacific Realm and the Central Indo-Pacific Realm. Pseudocaligus longipes Moon & Kim, 2012 is formally transferred to the genus Caligus as C. longipes (Moon & Kim, 2012) comb. nov.